1995
DOI: 10.1620/tjem.175.171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Cervical Cancer Screening: A Case-Control Study in Miyagi, Japan.

Abstract: To estimate the effectiveness of screening for invasive cervical cancer, a case-control study was performed in Miyagi, Japan. A total of 198 cases (129 mass screen-detected and 69 outpatient-detected) of invasive cervical cancer were identified between 1984 and 1990. The results of the Papanicolaou smear of these cases were compared to those of 396 age-(±5 years) and area-matched controls. Compared with women who had no prior screening (cases 51.6%, controls 16.2%), women who were screened had an odds ratio (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
(16 reference statements)
3
19
0
Order By: Relevance
“…[7][8][9][10][11][12] Case-control studies to date, though statistically underpowered, have suggested that some protection may be conferred, albeit of smaller magnitude than that offered for squamous malignancies. [17][18][19] This result is at odds with the epidemiologic trend and suggests that if an effect is present, it is likely to be small.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Case-control studies to date, though statistically underpowered, have suggested that some protection may be conferred, albeit of smaller magnitude than that offered for squamous malignancies. [17][18][19] This result is at odds with the epidemiologic trend and suggests that if an effect is present, it is likely to be small.…”
Section: Discussionmentioning
confidence: 99%
“…6,27 The effect of screening on incidence of invasive cervical cancer is shown in Appendix 5 (available at www .cmaj .ca/lookup /suppl /doi :10.1503 /cmaj.121505 / -/DC1). A meta-analysis of 12 case-control studies [28][29][30][31][32][33][34][35][36][37][38][39] showed that the odds of having undergone at least 1 Pap test were lower among women with invasive cervical cancer (OR 0.4, 95% CI 0.3-0.4, Appendix 5) than among women who did not have cervical cancer. A cohort study with a 3-year follow-up found that screening was associated with a decrease in incidence of cervical cancer (relative risk 0.4, 95% CI 0.2-0.6), 38 whereas a randomized controlled trial (RCT) from rural India found a nonsignificant effect of screening on incidence.…”
Section: Women Aged 30-69 Years For Women Aged 30-69 Years We Recommmentioning
confidence: 99%
“…Results of a case-control study conducted in Japan revealed that between individuals screened annually and biennially, there was a significant decrease in the rate of early detection in those who underwent biennial screenings (Morimura and Ito, 2005). Moreover, a 2-year prevention may be anticipated from a negative biennial cytodiagnostic result; thus, annual screenings are likely much more effective (Makino et al, 1995;Sato et al, 1997). Therefore, an investigation into restoring annual screening is warranted.…”
Section: Discussionmentioning
confidence: 99%